استخدام الكوميك (اي-جم) في حل مشكلة طلاب الصف الثالث في فهم معنى وسياق الحوار في منطقة كلانج بولاية سيلانجور: The Use of E-Jummu Comics in Solving Form 3 Students’ Problems in Understanding the Meaning and Context of Dialogue (Al-Hiwar) in Klang, Selangor - Ahmad Juhari, Muhammad Aidil Azhar (SIBAWAYH Arabic Language and Education, 2024)
تنفيذ هذه الدراسة كخطوة لمعالجة مشكلة فهم وتحقيق طلاب الصف الثالث في فهم معنى وسياق الحوار في اللغة العربية. إن القلق من التصورات السلبية تجاه هذه المادة دفعني للبحث عن حل مبتكر وفعال. شمل الاستطلاع الأولي للدراسة مراجعة أعمال الطلاب، والاختبارات الأولية، والاستبيانات، والمقابلات، والملاحظة، التي كشفت عن أن العديد من الطلاب يواجهون صعوبات في فهم معنى الحوار المقدم. في محاولة لتحسين القدرة على فهم الحديث، قررت تطبيق منهج الكوميك. قدمت طريقة e-Jummu التي تستخدم تقنيات قراءة الكوميك لمساعدة الطلاب على فهم معنى الحوار بسهولة أكبر. شملت الدراسة 30 طالبا، وتم تنفيذ 5 أنشطة تدريس وتعلم باستخدام هذا المنهج على مدى 8 أسابيع. أظهرت نتائج الاختبارات اللاحقة زيادة في أداء الطلاب في فهم الحديث. أبدى الطلاب اهتمامًا أكبر بهذه المادة نظرًا للنهج السهل والممتع. يوصى بمواصلة استخدام هذا المنهج في التدريس والتعلم لزيادة اهتمام الطلاب وتحقيقهم في فهم معنى وسياق الحوار باللغة العربية. This study was carried out as a step to overcome the problem of comprehension and achievement of 3rd grade students in understanding the meaning and context of dialogue (al-hiwar) in Arabic. Concern for the negative perception of this subject pushed me to find innovative and effective solutions. The initial review of the study involved reviewing student work, pre-tests, questionnaires, interviews, and observations, which revealed that many students faced difficulties in understanding the meaning of the dialogue delivered. In an effort to improve the ability to understand al-hiwar, I decided to apply a comic approach. I introduced the e-Jummu method which uses comic reading techniques to help students understand the meaning of dialogue more easily. The study involved 30 students, by carrying out 5 teaching and learning activities using this approach for 8 weeks. The results of the post test show an improvement in student performance in understanding al-hiwar. Students show higher interest in this subject because of its easy and entertaining approach. Teaching and learning using this approach is recommended to continue to increase students’ interest and achievement in understanding the meaning and context of Arabic dialogue. Keywords: comic, Ai technology, al-hiwar, dialogue